R-A-D-E-C: A LEARNING LANGUAGE PERSPECTIVE IN ELEMENTARY SCHOOL (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The goal of the study was to investigated how R-A-D-E-C step (Reading-Answer-Discuss-Explain-Create) by Sopandi integrated with language learning in Elementary Education. This study was qualitative descriptive research with observation and interview as an instrument. It explained the R-A-D-E-C Step and the four-language ability which are Listening, Reading, Speaking, and Writing. Based on this study, R-A-D-E-C learning model gives the children an opportunity to developed the language ability. R-A-D-E-C also optimize the function of the whole language learning approach in Elementary School.